Thyroid-associated ophthalmopathy: Using diffusion tensor imaging to evaluate visual pathway microstructural changes - Li, Rui; Li, Jing; Wang, Zhenchang (Frontiers in Neurology, 2022)
Objective The aim of this study was to determine whether the visual pathway is affected by thyroid-associated ophthalmopathy (TAO) before the development of dysthyroid optic neuropathy (DON) with diffusion tensor imaging (DTI). Materials and methods Fifty-seven TAO patients (22 mild, 35 moderate-severe TAO) and 30 healthy controls (HCs) were included. The DTI parameters of the lateral geniculate (LG) and optic radiation (OR) were measured. A full ophthalmic examination such as intraocular pressure, exophthalmos, and visual acuity was performed. Clinical activity scores (CAS) were also calculated. One-way ANOVA and Pearson's correlation were carried out. A binary logistic regression was used to identify variables that can diagnose TAO. Results Moderate-severe TAO patients showed significantly lower fractional anisotropy (FA) and higher mean diffusivity (MD) than HCs for both LG and OR (p < 0.05). FA of OR was negatively correlated with CAS and intraocular pressure (p < 0.05). Multivariate analysis showed that FA of LG and FA of OR were a significant predictor for the diagnosis TAO. Conclusion Diffusion tensor imaging parameters of the visual pathway were significantly altered in moderate-severe TAO patients. The FA of LG, in particular, can be used as a sensitive imaging biomarker for assessing subclinical visual pathway damage in TAO.